PEO of AZ31 Mg Alloy: Effect of Electrolyte Phosphate Content and Current Density - Hadzima, Branislav; Kajánek, Daniel; Jambor, Michal; Drábiková, Juliána; Březina, Matěj; Buhagiar, Joseph; Pastorková, Jana; Jacková, Martina (MDPI, 2020)
In this work, the quality of coatings prepared by plasma electrolytic oxidation (PEO) on an AZ31 magnesium alloy were evaluated. This was done by studying the effects of the chemical composition of phosphate-based process electrolytes in combination with different applied current densities on coating thickness, porosity, micro-cracking and corrosion resistance in 0.1 M NaCl. Both processing parameters were studied in four different levels. Mid-term corrosion resistance in 0.1 M NaCl was examined by electrochemical impedance spectroscopy and based on this, corrosion mechanisms were hypothesized. Results of performed experiments showed that the chosen processing parameters and electrolyte composition significantly influenced the morphology and corrosion performance of the prepared PEO coatings. The PEO coating prepared in an electrolyte with 12 g/L Na3PO4 center dot 12H(2)O and using an applied current density 0.05 A/cm(2) reached the highest value of polarization resistance. This was more than 11 times higher when compared to the uncoated counterpart.

In this work, the quality of coatings prepared by plasma electrolytic oxidation (PEO) on an AZ31 magnesium alloy were evaluated. This was done by studying the effects of the chemical composition of phosphate-based process electrolytes in combination with different applied current densities on coating thickness, porosity, micro-cracking and corrosion resistance in 0.1 M NaCl. Both processing parameters were studied in four different levels. Mid-term corrosion resistance in 0.1 M NaCl was examined by electrochemical impedance spectroscopy and based on this, corrosion mechanisms were hypothesized. Results of performed experiments showed that the chosen processing parameters and electrolyte composition significantly influenced the morphology and corrosion performance of the prepared PEO coatings. The PEO coating prepared in an electrolyte with 12 g/L Na3PO4 center dot 12H(2)O and using an applied current density 0.05 A/cm(2) reached the highest value of polarization resistance. This was more than 11 times higher when compared to the uncoated counterpart.
PEO of AZ31 Mg Alloy: Effect of Electrolyte Phosphate Content and Current Density
Keywords: magnesium alloy; plasma electrolytic oxidation; corrosion; magnesium alloy; plasma electrolytic oxidation; corrosion